1984
DOI: 10.1083/jcb.99.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid control of autophagic sequestration and protein degradation in isolated rat hepatocytes.

Abstract: Sequestration of the inert cytosolic marker [ 14C]sucrose by sedimentable organelles was measured in isolated rat hepatocytes made transiently permeable to sucrose by means of electropermeabilization . Lysosomal integrity, protein degradation, autophagic sequestration, and other cellular functions were not significantly impaired by the electric treatment .Hepatocytes sequestered sucrose at an initial rate of -10%/h, which is threefold higher than the estimated rate of auto phagic-lysosomal protein degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(94 citation statements)
references
References 37 publications
2
89
0
Order By: Relevance
“…The maximal rate of amino-acid-sensitive sucrose sequestration was 5% of the cytosolic volume in 60 min. Amino-acidinsensitive uptake of ['T]sucrose (60% of total sequestered sucrose) is due to accumulation of sucrose in mitochondria [18]. Values are the means (?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal rate of amino-acid-sensitive sucrose sequestration was 5% of the cytosolic volume in 60 min. Amino-acidinsensitive uptake of ['T]sucrose (60% of total sequestered sucrose) is due to accumulation of sucrose in mitochondria [18]. Values are the means (?…”
Section: Resultsmentioning
confidence: 99%
“…100 nM wortmannin (W), the 4Xcomplete mixture of amino acids (AA) or 5 mM 3-methyladenine (3MA). After 60 min of incubation, ["C]sucrose sequestration was measured as in [18]. The maximal rate of amino-acid-sensitive sucrose sequestration was 5% of the cytosolic volume in 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of amino acids do not, however, completely inhibit autophagic sequestration of [ 14 C]sucrose (Seglen & Gordon, 1984), even though they completely inhibit overall autophagic proteolytic flux. This indicates that amino acids also interfere with post-sequestrational steps.…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 98%
“…Electron microscopic studies (Schworer & Mortimore, 1979;Kovács et al, 1981) and data obtained with electro-injected cytosolic [ 14 C]sucrose and other sugars (Seglen & Gordon, 1984;Seglen & Bohley, 1992) have led to the conclusion that the inhibition of macroautophagy by amino acids primarily occurs at the sequestration step. High concentrations of amino acids do not, however, completely inhibit autophagic sequestration of [ 14 C]sucrose (Seglen & Gordon, 1984), even though they completely inhibit overall autophagic proteolytic flux.…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 99%
“…Physiologically, autophagy is induced by amino acid deprivation [18] . Electron microscopy studies have indicated that complete deprivation of serum and amino acids provides a useful model for the further study of cellular autophagy [19] .…”
Section: Starvation Inducersmentioning
confidence: 99%